2008
DOI: 10.1086/587623
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Advantageous Selection: Evidence from the Medigap Insurance Market

Abstract: Yale for many helpful suggestions. We are grateful to Mike Chernew for the access to, and Tami Swenson for clarification of, the Medicare Current Beneficiary Survey data. All remaining errors are our own. Fang and Silverman gratefully acknowledge financial support from the Economic Research Initiative on the Uninsured. The views expressed herein are those of the author(s) and do not necessarily reflect the views of the National Bureau of Economic Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
284
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(301 citation statements)
references
References 53 publications
15
284
2
Order By: Relevance
“…Indeed, recent empirical work has documented substantial preference heterogeneity in different insurance markets, including automobile insurance (Cohen and Einav, 2007), reverse mortgages (Davidoff and Welke, 2007), health insurance (Fang, Keane, and Silverman, 2008), and long-term care insurance (Finkelstein and McGarry, 2006). The existence of unobserved preference heterogeneity opens up the possibility of advantageous selection, which produces opposite results to the adverse selection results just discussed.…”
Section: Adverse and Advantageous Selection: A Graphical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent empirical work has documented substantial preference heterogeneity in different insurance markets, including automobile insurance (Cohen and Einav, 2007), reverse mortgages (Davidoff and Welke, 2007), health insurance (Fang, Keane, and Silverman, 2008), and long-term care insurance (Finkelstein and McGarry, 2006). The existence of unobserved preference heterogeneity opens up the possibility of advantageous selection, which produces opposite results to the adverse selection results just discussed.…”
Section: Adverse and Advantageous Selection: A Graphical Frameworkmentioning
confidence: 99%
“…Finkelstein and McGarry (2006) document advantageous selection in the market for long-term care insurance and provide evidence that more cautious individuals invest more in precautionary behavior and are less likely to use a nursing home, but at the same time are more likely to purchase long-term care insurance. Fang, Keane, and Silverman (2008) document advantageous selection in the market for Medi-gap coverage, which provides private health insurance that supplements Medicare for the elderly, but show that in the case of Medi-gap, cognition may be the driving force: individuals with higher cognitive ability are often able to make better decisions, which can translate into both greater coverage and at the same time lower health care expenditures.…”
Section: Adverse and Advantageous Selection: A Graphical Frameworkmentioning
confidence: 99%
“…Thus there is not a severe adverse selection in insurance market [18-20]. In addition, some studies revealed that there exists a positive selection in insurance market [21,22]. Then, how health status influences insurance enrollment rate in the market of the URBMI and the NCMS is a problem that needs to be studied in the further researches.…”
mentioning
confidence: 99%
“…Existing explanations for the oft-absence of adverse selection focus on preference heterogeneity (see Finkelstein and McGarry [2006] in LTC, Fang et al [2008] in Medigap, and Cutler et al [2008] for a broader focus across five markets). At a high level, these papers suggest that in some contexts the higher risk (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For Medigap, Fang et al [2008] find evidence of advantageous selection based on observables: individuals with observable health conditions are less likely to purchase Medigap insurance, despite having higher expected costs. However, their analysis not address the potential that rejections by Medigap insurers drive the lower ownership amongst those with observable health conditions.…”
mentioning
confidence: 97%